Power BI como herramienta de aplicación para el Análisis Financiero de la COAC “Ichubamba” Ltda., período 2022. - Usca Ordoñez, Erika Paola (2024)
ABSTRAC This study was carried out with the purpose of applying Power BI as a tool for the development of a Dashboard that would facilitate analyzing the financial situation of COAC "Ichubamba" Ltda. during the period 2022. The methodological process considered was based on an investigative approach mixed type, that is, qualitative and quantitative, characterized by the adoption of a descriptive and field method. Surveys and interviews were applied to COAC collaborators linked to the financial management of the COAC. Additionally, data on the financial situation was compiled, which was organized and processed using Power BI, thus generating a Dashboard that graphically and dynamically displayed financial parameters. The results show a growth in assets, going from 650171.72 USD in 2021 to 833254.15 USD for 2022. For its part, the income related to its operations in 2022 corresponded to 169228.21 USD. Regarding the opinion of the manager and collaborators surveyed, the agreement and favorable opinions regarding the use of the Dashboard were appreciated, since there was no tool available to facilitate the visualization and interpretation of data. The application of Power BI has effectively improved the role of financial situation analysis by using it as a strategic tool for COAC "Ichubamba" Ltda. The combination of efficiency, precision and improved decision making has facilitated financial analysis resulting in information important and indispensable for the fulfillment of the COAC's objectives, allowing it to adapt and respond quickly to the dynamics of the financial environment. Keywords: Power BI, automation, financial analysis, indicators, decision making.